2015
DOI: 10.1016/j.vaccine.2015.01.089
|View full text |Cite
|
Sign up to set email alerts
|

Inactivated polio vaccination using a microneedle patch is immunogenic in the rhesus macaque

Abstract: The phased replacement of oral polio vaccine (OPV) with inactivated polio vaccine (IPV) is expected to significantly complicate mass vaccination campaigns, which are an important component of the global polio eradication endgame strategy. To simplify mass vaccination with IPV, we developed microneedle patches that are easy to administer, have a small package size, generate no sharps waste and are inexpensive to manufacture. When administered to rhesus macaques, neutralizing antibody titers were equivalent amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
81
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(83 citation statements)
references
References 43 publications
(41 reference statements)
1
81
1
Order By: Relevance
“…Besides, an effort was made to find a dose sparing strategy for IPV immunization. However, intradermal and intramuscular immunization without use of adjuvants led to similar results, likewise as reported for other microneedle strategies: HMN in rats (8,11) or humans (13), coated microneedles in rats (9), dissolving microneedles in rats (10) or rhesus macaques (12). Furthermore, clinical trials in humans have been performed to investigate IPV dose sparing, by comparison of a 80% reduced IPV dose (20% of full dose) administered intradermally against a full IPV dose administered intramuscularly.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Besides, an effort was made to find a dose sparing strategy for IPV immunization. However, intradermal and intramuscular immunization without use of adjuvants led to similar results, likewise as reported for other microneedle strategies: HMN in rats (8,11) or humans (13), coated microneedles in rats (9), dissolving microneedles in rats (10) or rhesus macaques (12). Furthermore, clinical trials in humans have been performed to investigate IPV dose sparing, by comparison of a 80% reduced IPV dose (20% of full dose) administered intradermally against a full IPV dose administered intramuscularly.…”
Section: Discussionsupporting
confidence: 53%
“…Another novel strategy for intradermal injection is microneedles, which are micron-sized needles (7). Microneedles were investigated on their ability to induce protective immune responses upon intradermal IPV delivery on rats and rhesus macaques (8)(9)(10)(11)(12). Hollow microneedle (HMN) mediated intradermal IPV immunization at reduced doses was also investigated in humans, which resulted in similar seroconversion rates in comparison to a full intramuscular dose (13).…”
Section: Introductionmentioning
confidence: 99%
“…Effective cross-talk between innate and adaptive immune responses generates more robust, longer-lasting immune protection [20,21]. We and other investigators have previously reported that skin immunization with metal or dissolving microneedle patches (MNPs) carrying various vaccines (influenza, inactivated poliovirus (IPV), measles, tetanus, HPV, rotavirus, BCG, malaria and RSV) confers immune responses at least non-inferior to conventional immunization as shown by lethal challenge studies, longevity of immune responses and breadth of immunity in a number of small-animal models [21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…115,116 However, unlike hollow MN, a limitation is placed on the amount of vaccine that can be incorporated into the system 117 and vaccinees may be obliged to wait for extended periods of time to ensure complete MN degradation. 114 104 and polio 105 in rhesus macaques, with a long term aim to create a thermostable, selfadministration platform. Although an attractive platform, dissolvable microneedle (DMN) systems for vaccine delivery have required more time to reach clinical trials compared to hollow or solid microneedles.…”
Section: Dissolving Microneedlesmentioning
confidence: 99%